Influence of Tumbling Bodies on Surface Roughness and Geometric Deviations by Additive SLS technology - Lichovník, Jiří; Mizera, Ondřej; Sadílek, Marek; Čepová, Lenka; Zelinka, Jan; Čep, Robert (Manufacturing Technology Journal, 2020)
This research focusing on influencing the surface structure and its geometric deviations from the CAD model after various tumbling of bodies at constant parameters of the tumbling machine. The purpose of determining the actual effect on the resulting surface before and after the tumbling pro-cess, which tumbling body causes the selection of a larger grain or compaction of the surface layer. The research outputs are thermographic maps and geometric deviations measured using CAD mod-els. The experimental line was at VŠB - TU Ostrava, with the help of the PROTOLAB 3D printing center, there was an experimental sample in your game. Measurement of access in the metrology laboratory on CMM Wenzel LH 65 X3Premium and optical heads Shapetracer II.
Keywords: 3D CMM; Optical scanning; Geometric deviations; Aditive Technology; Method S